High prevalence of undernutrition and low dietary diversity in institutionalised elderly living in Sri Lanka. Issue 15 (1st April 2015) - Rathnayake, Kumari M; Wimalathunga, MPPM; Weech, Michelle; Jackson, Kim G; Lovegrove, Julie A
Abstract: Objective: The present study aimed to assess nutritional status, dietary diversity and lifestyle risk factors associated with undernutrition in an institutionalised Sri Lankan elderly population. Design: The study was of cross-sectional design followed by a stratified sampling method. Setting: Twelve homes for the elderly recruited from six provinces in Sri Lanka. Subjects: A total of 311 institutionalised elderly aged ≥60 years. Results: The mean age of the study population was 75 (sd 8) years. Prevalence of undernutrition was 30 %. Mean food variety score, dietary diversity score and dietary serving score of the study population were 8·7 (sd 1·5), 7·3 (sd 1·2) and 10·9 (sd 2·0), respectively. Mean daily intakes of fruit, vegetables, meat, fish, eggs and pulses and dairy portions were below the national recommendations, whereas the mean consumption of sugar exceeded the national recommendation. Only the mean intake of starch was within the recommendation. Food allergies (OR=8·0; 95 % CI 3·9, 16·2), skipping meals (OR=3·8; 95 % CI 2·0, 7·5) and lack of leisure activities (OR=3·1; 95 % CI 1·5, 6·7) significantly increased the risk of undernutrition, whereas the use of dentures decreased the risk (OR=0·20; 95 % CI 0·06, 0·69). Conclusions: High prevalence of undernutrition and low dietary diversity were observed in an institutionalised elderly Sri Lankan population. Therefore, there is an urgent need to implement nutrition interventions as part of geriatric care to reduce undernutrition and improve the diets of the institutionalised elderly population in Sri Lanka.